2005
DOI: 10.1677/joe.1.05889
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone (DHEA) modulates GHRH, somatostatin and angiotensin II action at the pituitary level

Abstract: In view of the present controversy related to the potential beneficial effects of clinical dehydroepiandrosterone (DHEA) treatments, and considering our own previous results that reveal an influence of this steroid in pituitary hyperplasia development in vivo in rats, we decided to evaluate the role of DHEA in prolactin and GH secretion, as well as in second messengers involved, in cultured rat anterior pituitary cells. DHEA (1 10 5 to 1 10 7 M) did not modify basal GH or prolactin release, and a prolactin inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…This study reports that DHEA administration for 2.5 d significantly enhanced serum GH (1 h after GHRH exposure), and this correlated well with the significantly increased expression of GH proteins and GHRH receptivity (detected by binding to biotinylated GHRH). Our in vivo studies agree with a recent report by Suarez et al (50), who showed that DHEA potentiated GHRH-induced GH release (not basal GH release) by modulating cAMP production in cultured young rat AP cells.…”
Section: Discussionsupporting
confidence: 93%
“…This study reports that DHEA administration for 2.5 d significantly enhanced serum GH (1 h after GHRH exposure), and this correlated well with the significantly increased expression of GH proteins and GHRH receptivity (detected by binding to biotinylated GHRH). Our in vivo studies agree with a recent report by Suarez et al (50), who showed that DHEA potentiated GHRH-induced GH release (not basal GH release) by modulating cAMP production in cultured young rat AP cells.…”
Section: Discussionsupporting
confidence: 93%